Fiber composites as a method of treatment splinting tooth mobility in chronic periodontitis - Dewi L. Ichwana (Journal of Dentomaxillofacial Science, 2016)
Patients with periodontal disease can lead to severe tooth mobility so often complains of pain when eating, decreased chewing ability and functional occlusion. Tooth mobility is a movement in a horizontal or vertical direction and one of the most unpleased effects from periodontal disease. Basically, tooth mobility is not a disease that requires treatment, but it is a symptom of periodontal tissue morphology changes, so it became a challenge for dentists in making decisions to maintain proper care of the teeth. Recent studies improved the use of periodontal splint with fiber reinforced composite (FRC) or fiber composite may lead to a long-term prognosis of teeth mobility due to periodontal disase. The case report describes treatment of chronic periodontitis patients with splinting fiber composites as a method for stabilization of the lower anterior teeth providing aesthetics, comfort, improved functionality occlusion, mastication and a good prognosis.